A Model-free CAF Fringe Search Algorithm with Wavelet Boosting for VLBI Observation. (23rd May 2017) - Zhang, Tianyi; Meng, Qiao; Chen, Congyan; Zheng, Weimin; Liu, Wei; Yu, Quantao; Tong, Li
Abstract: Very-Long-Baseline interferometry (VLBI) is a powerful tool in radio astronomy, geodesy, and deep space exploration. Priori predicted delay models are needed to make interferometry fringes, but in some cases they would be difficult to get. This paper proposes an effective algorithm named CAF-W algorithm to search fringes from the raw data in a large search range without priori predicted delay models. The cross-ambiguity function (CAF) is used to make a time-frequency correlation in the delay–delay rate plane. The wavelet boosting algorithm is used to eliminate interference and enhance the CAF peak, whose position would give the delay and delay rate estimations. Incoherent averaging and sliding search window techniques are used to overcome the wide search range and the poor signal-to-noise ratio in VLBI observations. The CAF-W algorithm could be performed with fast algorithms so the computation burden is affordable. This algorithm has successfully achieved VLBI fringes from the raw data without priori predicted delay models in VLBI observations.